Soil quality restoration and yield stabilization in acidic soils of northeastern Himalayas: Five years impact of green manuring and crop residue management - Ansari, Meraj A.; Babu, Subhash; Choudhary, Jairam; Ravisankar, Natesan; Panwar, Azad S. (Frontiers in Environmental Science, 2022)
Soil quality restoration and crop productivity maximization are the global challenge to feed the galloping population. The task is much more daunting in a risk-prone, fragile, and low productive hilly region due to the depletion of supporting and regulating ecosystem services. A five-year long-term (2012–2017) field experiment was conducted to stabilize the yield and soil quality through legume green manuring and crop residue recycling in intensified cropping systems in the Eastern Himalayan region of India. Four treatments involving three green manures [green gram (Vigna radiata); cowpea (Vigna unguiculata); Sesbania (Sesbania aculeata) along with control (no-green manure)], three cropping systems [groundnut (Arachis hypogaea)—pea (Pisum sativum); maize (Zea mays)—pea, and maize + groundnut–pea] and two levels of residue management practices [residue removal and residue retention] were evaluated in three times replicated split–split plot design. Among the green manure options, Sesbania exerted a significant positive impact on the soil organic carbon (SOC) stock, available micro- (Fe, Mn, Zn, and Cu), and macronutrients (N, P and K) in surface (0–0.15 m) and subsurface (0.15–0.45 m) soils. The improvement in soil enzymatic activities (acid phosphatase, alkaline phosphatase, dehydrogenase, beta-glucosidase, and aryl sulfatase activity) (p < 0.05) in Sesbania-treated soil was +28.1% to +38.9% in surface and +18.3% to +27.3% in subsurface soils over non-green manure. Sesbania-treated soils also exhibited higher soil quality index (SQI) and stratification ratio (SR) of available soil nutrients and enzymes over non-green manured soils. Among the cropping systems, groundnut intercropped with maize followed by peas (MGP) with in situ residue retention increased (p < 0.05) the available soil macro- and micronutrients, SOC stock, soil enzymes, SR, and SQI in comparison to other cropping systems. Sesbania green manuring and residue retention improved the yield sustainability by +19% and +11% in the MGP system over non-green manuring and residue removal, respectively. Therefore, Sesbania green manuring in the MGP cropping system along with residue retention is recommended for stabilizing the soil quality through enhancing supporting and regulating ecosystem services and maintaining long-term productivity in the fragile Eastern Himalayan ecosystem of India.